Design of Internet of Thought-assisted Telemetry System for Vehicle Parameter Monitoring System - Sidik, Rahman; Rahmy Jasril, Ilmiyati; Jaya, Putra (Universitas Negeri Padang, 2025)
The rapid development of digital technology encourages the important role of telemetry systems in monitoring various vehicle parameters in real-time. This research aims to design and develop an ESP32 microcontroller-based vehicle telemetry system integrated with several sensors. The sensors used include INA219 sensor to monitor battery voltage and current, MAX6675 sensor to measure engine temperature, and Neo-6M GPS module to determine the position and speed of the vehicle. The measurement results are displayed directly on the LCD screen and sent to IoT platforms such as ThingSpeak and Blynk Legacy via internet connection using WiFi network or SIM800L-based GSM network. The IoT platform serves as a medium for remote data storage and display. This system has been tested on Honda Supra Fit X motorcycle in static and dynamic conditions. The test results show that the system is able to accurately measure vehicle parameters with a small deviation rate compared to standard measuring instruments, namely ±1.0°C for temperature using a SmartSensor AR320+ infrared thermometer and 0.3V for voltage using a Sanwa CD800a digital multimeter. The data transmission system also proved to be stable under various network conditions. This telemetry system offers an efficient, flexible and accessible vehicle monitoring solution to support safety and preventive maintenance.